Menguatnya Ikatan Patronase dalam Perpolitikan Indonesia - Dina Fadiyah; Ummi Zakiyah (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2018)
This paper intends to see how the strengthening of patronage ties in Indonesian politicstoday is strengthened. The political euphoria in Indonesia is increasingly interesting, thearticle of political essence that occurs is not only about pure politics, but has beencontaminated with various elements and interests. This is what makes the political elitemust have a precise strategy to strengthen their position. This paper uses qualitativemethods, descriptive and found that the strengthening of patronage ties in Indonesianpolitics is caused by mutual need or mutualism symbiosis between political elites andvarious elements such as community organizations for example.